The Student-Teachers’ Understandings of EIL Approach in A Microteaching Course - Ardiyani Widya (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
This paper presents a study about the students-teachers’ understandings of EIL approach inthe three mini lessons which includes one of the topics requirement: integratingmulticultural approaches to provide small and medium enterprises with competitiveadvantage. In particular, the study aims to find what eight student-teachers’ understandingsof EIL approach are in a Microteaching course (ED603C). English is defined as anInternational Language (EIL) approach as the situation where “English is used tocommunicate across linguistic and cultural boundaries, often in more formal contexts, thenthere seems little reasons to require these boundaries must coincide with national borders”.From this definition, it can be implied that English has been used for the objective of widercommunication purposes for people all over the world. The data were collected throughlesson plans, Action Research Teaching Journals (ARTJs), and portfolios. The study foundthat there were three prominent themes where EIL approach is defined. First, the studentteachersgot their initial understanding of EIL approach as comparing two cultures (westernand local cultures). Second, the student-teachers got better understandings of EIL byaccommodating their students’ cultures. Third, the student-teachers had finallyaccommodated EIL approach by presenting not only local and target language cultures, butalso international cultures. In addition, presenting various kinds of cultures were claimed tobe a successful way to increase their students’ interest of the materials as well as theirstudents’ awareness of cultural diversities. It is expected that this research will give betterunderstanding to the development and implication of EIL approach in the future. The paperends with some recommendation for improvement of EIL approach and other multiculturalapproaches.Keywords: student-teachers; EIL approach; microteaching course; target language cultures;international cultures